Thermal analysis of two-phase closed thermosyphon (TPCT) using nanofluids. (2020) - Suresh kumar, R.; Tharves Mohideen, S.; Jayanthi, N.; Venkatesh, M.
Abstract: In this study, the thermal performance of two-phase closed thermosyphon (TPCT) using Al2 O3 (<50 nm) nanoparticle with base fluid distilled water is presented. The TPCT is fabricated from the copper tube with the outer diameters and length of 6 mm, 8 mm, and 800 mm, respectively. The concentration of nanofluid is varied from 3% and 4% by weight. The experimental work is carried out under different operating conditions. The input parameters such as effects of heat input, fill ratio, and nanoparticle concentration on the thermal efficiency and thermal resistance of the TPCT were investigated, compared and discussed. From the results, it is observed that for different heat inputs, the efficiency of the TPCT increases when Al2 O3 /water nanofluid was used instead of water.